Toward better understanding of postharvest deterioration: biochemical changes in stored cassava (Manihot esculenta Crantz) roots - Gavicho Uarrota, Virgílio; Costa Nunes, Eduardo da; Martins Peruch, Luiz Augusto; Oliveira Neubert, Enilto de; Coelho, Bianca; Moresco, Rodolfo; García Domínguez, Moralba; Sánchez, Teresa; Luna Meléndez, Jorge Luis; Dufour, D.L.; Ceballos, H.; Becerra López Lavelle, Luis Augusto; et al. (Wiley, 2015)
Food losses can occur during production, postharvest, and processing stages in the supply chain. With the onset of worldwide food shortages, interest in reducing postharvest losses in cassava has been increasing. In this research, the main goal was to evaluate biochemical changes and identify the metabolites involved in the deterioration of cassava roots. We found that high levels of ascorbic acid (AsA), polyphenol oxidase (PPO), dry matter, and proteins are correlated with overall lower rates of deterioration. On the other hand, soluble sugars such as glucose and fructose, as well as organic acids, mainly, succinic acid, seem to be upregulated during storage and may play a role in the deterioration of cassava roots. Cultivar Branco (BRA) was most resilient to postharvest physiological deterioration (PPD), while Oriental (ORI) was the most susceptible. Our findings suggest that PPO, AsA, and proteins may play a distinct role in PPD delay.